MASSAGE THERAPY AS AN ALTERNATIVE FOR TODDLER ACUTE RESPIRATORY INFECTION (ARI): A CROSS-SECTION STUDY - Lasiyati Yuswo Yani; Mahmudah ,; Indra Yulianti (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Background: Acute Respiratory Infection (ARI) is highly contagious and can be experienced by anyone, especially children and the elderly. In most cases, ARI is caused by virus and can heal on its own without special treatment. However, parents cannot let this condition go too long because the children will feel uncomfortable. This study aims to determine the trend of massage therapy as an alternative therapy for ARI in toddlers. Methods: This quantitative cross-sectional study was conducted in a village in Mojokerto. The sample from this study were 70 parents who had children under 5 years old who were experiencing ARI. The research instrument used has been tested for validity with results and reliability with results. Furthermore, the data was tested statistically with the Spreaman test. Result: 52% of parents provide complementary massage therapy as a complement to medical treatment for their children, 45% provide medical therapy only, the rest provide self-medication. Conclusion: Most parents assume that medical treatment alone is not enough to seek treatment for ARI in children. The wedge massage complementary therapy is an alternative to complementary medical treatment which is seen as accelerating the healing process of ARI in children.